Privacy-deprived e-commerce: the efficacy of consumer privacy policies on China's e-commerce websites from a legal perspective. Issue 6 (20th August 2020) - Zhu, Ruilin; Srivastava, Aashish; Sutanto, Juliana
Abstract : Purpose: Despite grave public concerns over information privacy and ongoing academic explorations of privacy policy, there is a general lack of understanding toward this issue in the legal context in China, the largest e-commerce market in the world. Departing from the extant literature of general discussion in nature, the authors undertook an exploratory study on the efficacy of e-commerce websites' privacy policies in China from the legal perspective. Design/methodology/approach: The authors drew on a qualitative grounded theory approach to identify selective codes relating to the focal issue and established a theoretical framework therefrom. The authors then conducted theoretical integration by linking them to the Theory of Development Blocks and the System Justification Theory. Findings: The research identifies a general distrust of Chinese consumers toward privacy policies and highlights that despite their growing concerns about privacy, the privacy policies are largely ineffective in reflecting legal enforcement, changing their perceptions or influencing purchase behaviors. It also reveals that the current Chinese legislation is unable to fully render consumers' confidence in e-commerce websites' privacy policies effectiveness and privacy protection due to its limited recognition and influences among them. Originality/value: The research has multiple ramifications. The authors empirically confirmed a mismatch between customers' perception of privacy policies and their actual behaviors and then theoretically explained the seemingly conflicting scenario in the context of development block of legal enforcement and system justification. The authors theorized the absence of the legal enforcement in privacy policies to supplement the legal perspective to the literature. The research further leads us to suggest that the time has come to update and strongly enforce privacy regulation in China to fuel the further development of e-commerce sector in practice.